Special IMM groups. Issue 2 (3rd November 2022) - Groves, Daniel; Manning, Jason Fox
Abstract: Italiano–Martelli–Migliorini recently constructed hyperbolic groups which have non‐hyperbolic subgroups of finite type. Using a closely related construction, Llosa Isenrich–Martelli–Py constructed hyperbolic groups with subgroups of type F 3 F_3 but not F 4 F_4 . We observe that these hyperbolic groups can be chosen to be special in the sense of Haglund–Wise.